Adsorption isotherms of raw and roasted hazelnuts - Guzey, D.; Ozdemir, M.; Seyhan, FG; Dogan, H.; Devres, YO (Informa UK Limited, 2001)
Adsorption isotherms of raw and roasted (at 100°C, 120°C, 140°C and 160°C) hazelnuts of Tombul variety were determined at 25°C, and over relative humidities ranging from 11 to 90% using the gravimetric static method. Eleven sorption models (GAB, BET, Modified BET, Halsey, Iglesias-Chirife, Oswin, Chung-Pfost, Smith, Kuhn, Harkins-Jura and Caurie) were evaluated by using the linear regression method. GAB (Guggenheim-Anderson-de Boer) model satisfactorily described adsorption characteristics of the samples over the experimental range of study. Monolayer values at 25°C were estimated from the GAB model as 0.0155 kg water/kg dry solid for raw and 0.0100–0.0163 kg water/kg dry solid for roasted hazelnuts. Caurie security moisture content for raw hazelnuts was also determined from Caurie model as 0.048 kg water/kg dry solid.